STRUKTURASI KEKUASAAN & KEKERASAN SIMBOLIK DALAM JIWA-JIWA PEMBERONTAK KARYA KHALIL GIBRAN: PERSPEKTIF PIERRE BOURDIEU - Sinar Ansar; Andi Karman; Aslan Abidin; Usman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the representation of power structuration and symbolic violence in Khalil Gibran’s short story collection Spirits Rebellious (Jiwa-Jiwa Pemberontak) using Pierre Bourdieu’s theoretical framework. Through descriptive qualitative analysis, this research identifies how Bourdieu’s four forms of capital (economic, social, cultural, and symbolic) are distributed among agents in the represented social arena, how the rebellious habitus is formed as a response to symbolic domination, and how symbolic violence is exercised through mechanisms of euphemism and censorship. The findings show that Spirits Rebellious not only represents the structuration of power in traditional Lebanese society but also offers the possibility of heterodoxy through symbolic resistance practices carried out by its rebellious characters. The novelty of this research lies in the systematic application of Bourdieu’s perspective to Gibran’s early work, which has been underexplored in Indonesian literary criticism, as well as its contribution to enriching the sociology of literature through the Bourdieusian approach.